Dense and Green Building Typologies Research, Policy and Practice Perspectives - Schröpfer, Thomas; Menz, Sacha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
In this book, academics, policy makers, developers, architects and landscape architects provide a systematic review of the environmental, social, economic and design benefits of dense and green building types in high-density urban contexts and discuss how these can support higher population densities, higher standards of environmental sustainability and enhanced live ability in future cities.
Introduction -- Creating Liveable Density through a Synthesis of Planning, Design and Greenery -- Building a City in Nature -- From Garden City to City in a Garden and Beyond -- Greenery in Commercial Buildings - Enhancing Returns for Investors? -- Green Buildings and the Homebuyers -- Emulating Ecosystems Ability to Provide Ecosystem Services in the Built Environment -- Biophilic Architecture to Biophilic Cities -- Prototypology and the 21st Century City -- The Role of Ecosystem Services in Making Cities Sustainable -- RGB: Red Blue Green Model as the "Lightness" of Being -- Taking Urban Greening to a Higher Level -- MPKL's Investigation -- Punggol Waterway Terraces -- Green Architecture: Landscape Topology and Context.
Keywords: Sustainable architecture; Human geography; Buildings -- Design and construction; Sustainability; Computer-aided engineering; Building materials; Sustainable Architecture/Green Buildings; Human Geography; Building Construction and Design; Sustainability; Computer-Aided Engineering (CAD, CAE) and Design; Structural Materials